Decarboxylative nucleophilic difluoromethylation of aldehydes and imines. Issue 32 (9th August 2018) - Chen, Jia; Lin, Jin-Hong; Xiao, Ji-Chang
Abstract: The high demand for the biologically active CF2 H-molecules has stimulated significant efforts to develop efficient methods for the installation of CF2 H functionality. We found that phenylsulfonyl difluoroacetate salt (PhSO2 CF2 CO2 − K + ) could directly undergo decarboxylation under warming conditions to produce active anion (PhSO2 CF2 − ) without the need of any base or additive, thus allowing for the subsequent nucleophilic (phenylsulfonyl)difluoromethylation of aldehydes or imines to give PhSO2 CF2 -alcohols or -amines, respectively. Interestingly, the removal of PhSO2 group was achieved simply by elevating the reaction temperature for the conversion of aldehydes to afford CF2 H-ketones. Graphical abstract: